Tribological properties study of lubricants for possible nanoclays reinforced biomedical applications (2020)
This research focuses on the use of nanoparticles halloysite nanotube (HNTs) and montmorillonite (MONT) to improve lubricating properties of polyethylene glycol (PEG) for total knee arthroplasty (TKA). Tribological tests nanofluids under Tribotester T-02U were performed using the ASTM D4172 standard changing the test temperature at 36 ° C-37 ° C, the analysis was made from the coefficient of friction (COF) and diameter worn (WSD) provided by the inspection worn mark on the optical microscope Alicona. There was a clear reduction of COF by 27% at 0.05% HNTs and WSD by 10% at 0.1% HNTs. However in MONT implementation COF is reduced by 6% at 0.05% concentration and WSD 2% at 0.01% concentration. In conclusion we obtained that nanoparticles HNTs improve the properties of PEG in greater proportion than nanoparticles MONT, although emphasis on further studies in tribological applications in bioengineering industry with both materials, due to their biological and physicochemical properties, is made. Cytotoxicity tests that ensured the biocompatibility of the nanoparticles with C6 rat glioma cells were performed.